KEMAMPUAN GURU IPA DALAM MENUMBUHKAN NILAI KARAKTER SISWA PADA MTSN DI ACEH - Wati Oviana Oviana; wati oviana (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2020)
One of the National education goals leads to the development of a student’s character value. Unfortunately, almost all educational processes at schools emphasize on improving cognitive aspects. This has slowed the student’s character value development. This research provides an illustration of science teachers in nurturing the character values of MTsN students in Aceh. The study adopted a descriptive method with a quantitative approach. The data were collected through analysis of lesson plan documents, classroom observations, and interviews. The result of the study indicated that the teachers showed high competence in nurturing students’ personality aspects at the lesson planning state in which all of the teachers were intelligent to include five-character values that need to be developed. However, not all teachers were competent in activating all character values during the classroom teaching and learning process. All teachers who were observed in all aspects of the investigation had successfully activated religious value, nationalism, and independence. On the other hand, the value of communal work and integrity were stimulated by only some of the teachers.